ERGONOMIC ANALYSIS OF PRUNING TREES IN CONFLICT WITH POWER LINES - Santos, Nayane Amaral; Freitas, Luís Carlos de; Fiedler, Nilton César; Leite, Elton Silva (Floresta, 2023)
Ergonomic analysis of pruning trees in conflict with power lines. Pruning trees in conflict with power lines is associated with several ergonomic risks due to postural issues and exposure to environmental conditions, such as noise and vibration in work activities. Additionally, there are life-threatening risks from falls or contact with power lines. The objective of this work was to apply the Ergonomic Workplace Analysis (EWA) method and assess the exposure of workers involved in pruning of trees conflicting with power lines to noise and vibration. The survey was conducted considering outsourced employees that provide services to an electric utility company in the state of Bahia, Brazil. The results obtained through EWA showed a regular risk rate, with concerning aspects, such as verbal communication (dialogue among workers regarding technical/operational issues), irregular posture of back, arms, and shoulders, high attention demand, and activity limitations. Quantitative analysis showed 84.9 dB (A-weighted) for noise and 2.440 m s-2 for vibration, both close to the action level. The pole saw vibration reached 3.703 m s-2, exceeding the tolerance limit. The importance of breaks, at-work exercises, and training is emphasized as ergonomic measures. A rotation system should be implemented in tree pruning activities to reduce exposure to vibration